AN ANALYSIS OF MEANING NEGOTIATION STRATEGY BETWEEN LECTURE-STUDENTS IN ENGLISH ONLINE CLASSES DURING PANDEMIC COVID-19 - Ririn Danari (Journal of English Education Program (JEEP), 2020)
This study is about Meaning negotiation that aims at investigating the type and strategies of meaning negotiation from Lectures and Seniors in English Online Classes during pandemic covid-19. Meaning negotiation show the students how to get the interaction with communication in conversation and the lectures strategies to have a good interaction with students. The aims of this research is to find out the type and strategies of meaning negotiation from lectures and students in Galuh University and reason the writer have this research is the writer want to students more confident and brave to speak up, ask and have an interaction and the lecture have a strategies to make a good interaction with the students. A qualitative design in which case study was employed in this study. The participants is the seniors and lectures from English Education Departmen Program and the data were collected by interviews use Google form and audio as the instruments. The results of the data is The Seniors of English Education Department Program use three from five categories signal of meaning negotiation focused by the writer, it is clarification check, confirmation check and repetition and the strategies of a humors related to the material with give the students example of English function and English expression before them speak up is the strategy of Lecture to have a meaning negotiation in English Online classes. This reseach concludes that meaning negitiation is important for the academic people to have a good communication.Keyword : Meaning negotiation